2014
DOI: 10.1007/s11011-014-9630-4
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade chronic inflammation induces behavioral stereotypy in rats

Abstract: Schizophrenia is known to be associated with metabolic disturbances including diabetes mellitus, obesity and cardiovascular diseases. A growing body of evidence has suggested abnormal cytokine levels in schizophrenia. In the present study, we explored the effects of low-grade chronic inflammation on behavioral stereotypy in a rat model of non-alcoholic fatty liver disease (NAFLD). In order to induce NAFLD, rats were fed with either water enriched with 30 % fructose or plain tap water for 8 weeks. Following fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Apomorphine‐induced stereotypy is a convenient method used in vivo tests for evaluating the effects of dopamine agonists or antagonists as well as for the assessment of dopaminergic activity (Erbaş et al, 2015). Apomorphine (1.5 mg/kg subcutaneously) was administered to all animals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apomorphine‐induced stereotypy is a convenient method used in vivo tests for evaluating the effects of dopamine agonists or antagonists as well as for the assessment of dopaminergic activity (Erbaş et al, 2015). Apomorphine (1.5 mg/kg subcutaneously) was administered to all animals.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we have reported that long‐term fructose‐received adult rats revealed significantly higher stereotypy score, elevated levels of brain and liver cytokines and brain dopaminergic activity than those of their normal controls (Erbaş et al, 2015). In the present study, we aimed to investigate the neurodevelopmental effects of long‐term maternal metabolic deterioration on offspring using a rat model of fructose‐induced metabolic syndrome.…”
Section: Introductionmentioning
confidence: 96%
“…Adipose tissue 3-fold change (↑) (mRNA) [37] BAL No change (→) (Protein) [42] Brain Control: 0.2 ng/mg Affected: 0.7 ng/mg (↑) (Protein) [36] Kidney 10-fold change (↑) (mRNA) [43] Liver 3-fold change (↑) (mRNA) [38] No change (→) (mRNA) [37] Control: 0.7 ng/mg Affected: 1 ng/mg (↑) (Protein) [36] Myocardium 2-fold change (↑) (mRNA) [45] Plasma Control: 4 pg/mL Affected: 10 pg/mL (↑) (Protein) [39] No change (→) (Protein) [57] Tumor necrosis factor soluble receptor II (TNF-sRII) [36] Liver Control: 10 pg/mL (→) (Protein) [36] IκB kinase (pIKK) Peritone 4-fold change (↑) (mRNA) [46] Mechanistic target of rapamycin (mTOR) Liver Control: 3 ng/mg Affected: 6 ng/mg (↑) (Protein) [52] Protein kinase B (AKT) Adipose tissue 1.5-fold (↓) (mRNA) [41] No change (→) (Protein) [58] LPS presenting protein Despite the fact that we have not attempted to be exhaustive in this review, significant diversity can be observed among the molecular biomarkers of inflammation listed in Table 1. Cytokines and chemokines are by far the most studied molecules, and IL-6, TNF-α, and MCP-1 figure among the most studied biomarkers in dietary studies with animal models.…”
Section: Proinflammatorymentioning
confidence: 99%
“…14, 21 However, there is still much to be clarified about the molecular mechanisms that induce changes at the level of the central nervous system. A bidirectional and robust interaction between the inflammatory process and different comorbidities has been established.…”
Section: 20mentioning
confidence: 99%